A FANTASIA DO REAL NO CONTEXTO DA EDUCAÇÃO INFANTI: ENTRE SONHOS E POSSIBILIDADES DE TRANFORMAÇÃO - Tony Aparecido Moreira; Denise Watanabe; José Milton de Lima; Márcia Regina Canhoto de Lima (Universidade do Oeste Paulista, 2013)
This research has surged from the finding that exists a lack of solid knowledge in relation of the children's imaginary, above all, in a educational perspective. The Professors don't know the real importance of the child's fantasy and the methods to work this language. The objective of this investigation consisted in bring up data about the real of fantasy, that represents the child's imaginary language, and even found ways for it's contemplation in the sphere of children's education. The research had qualitative nature and utilized as method the intervention research, have viewing the necessity of intrude the imaginary activities in the institution reality and prove the ideas according with the experiences observed and lived. The data were collected by a close accompaniment of a 5 year old class children in a Institution of Children's Education of the President Prudente's city-SP, counting with the participation of other people. The Children's Sociology represents the principal academic feedback of this investigation. The results generated represents the transformation of conceptions about the Children's fantasy, the achievement of ways for it's valorization inside the pedagogic practice and the proof of the importance of the imaginary experiences in children's life and education of the investigated institution.